Making Science Fun - A Tribute to Our Colleague and Friend, Prof. Antonius G. Rolink (1953-2017) - Rhodri Ceredig (Frontiers Research Topics, 2019)
This Research Topic honors the memory of Prof. Antonius "Ton" G. Rolink (April 19, 1953-August 06, 2017), our colleague, mentor and friend in immunology. It is now over a year since Ton left us. This article collection, authored by many of Ton's friends and colleagues, reflects the huge contribution to cellular and molecular immunology that work emanating directly from Ton's own hands and laboratory have made to the understanding of lymphocyte development. Ton's hard work, expertise, generosity, passion for science and infectious humor were legendary and for all of those lucky enough to have been his colleague, he ensured that science was fun. We take this opportunity of thanking all contributors for submitting their manuscripts; we are sure that Ton would have enjoyed reading and making his own insightful comments on them. In the form of original research and review articles, these papers cover many of Ton's scientific interests in different aspects of lymphocyte development in mouse and man. In the first section, Development of hematopoietic cells and lymphocytes, Klein et al. describe the accumulation of multipotent hematopoietic progenitors in peripheral lymphoid organs of IL-7xFlt3L double transgenic mice and Pang et al. the role of the transcription factor PU.1 on the development of Common Lymphoid Progenitors. In Early B cell development, Winkler and Mårtensson review the role of the Pre-B cell receptor in B cell development and papers by Hobeika et al. and Brennecke et al. describe models of inducible B cell development. For B cell selection, survival and tolerance, Smulski and Eibel review the role of BAFF and Kowalczyk-Quintans et al. analyse the role of membrane-bound BAFF. The impact of BIM on B cell homeostasis is discussed by Liu et al. The role of the MEK-ERK pathway in B cell tolerance is discussed by Greaves et al. and the transcriptional regulation of germinal center development is reviewed by Song and Matthias. For Hematological diseases, Ghia reviews how studies of B cell development help the understanding of Leukemia development, Kim and Schaniel review how iPS technology helps the understanding of hematological diseases and Hellmann et al. describe development of new therapeutic antibody drug conjugates. Finally, in T cell development, homeostasis and graft vs. host disease, Heiler et al. describe the therapeutic effects of IL-2/anti-IL-2 immune complexes in GvHD, Calvo-Asensio et al. describe the DNA damage response of thymocyte progenitors and Mori and Pieters review the role of Coronin 1 in T cell survival.